Perubahan Permukiman Perdesaan Pesisir Kabupaten Gunung Kidul Daerah Istimewa Yogyakarta Tahun 1996-2003 - Ritohardoyo, Su (Universitas Muhammadiyah Surakarta, 2007)
One of the impacts of coastal region development is settlement change. Because of that, this article presents a result of research about changing of settlement land area, house buildings, settlement facilities since 1996 up to 2003, and several factors which influence to the changing. This research was carried out in 20 karst villages borders on Indian Ocean so-called coastal villages in of Gunungkidul Regency as analysis units. Data analysis employs so-called secondary data analysis method, using Village Potentials Cencus (PODES) data were published in Statistics Central Bureau. Data analysis employs frequency, cross tabulations, and statistical analysis. Result of this research shows that as long as 1996 up to 2003 the settlement land area increases on 0.24 % per annum on an average, while the house building number on 6.14 % per annum. Spatially several coastal rural villages are near or as a tourism object or as a district office locations are higher developing than the others of coastal rural villages. It means that the development of tourism objects as long as 1996 up to 2003 has influenced the coastal rural settlement development. Generally, the development of coastal rural settlement is significantly also influenced by thirteen of physical and socio-economical factors (R=0.903; Sig.=0.05). In detail however, among the 13th of physical and socio-economical factors are only five factors significant influence to the development of coastal rural settlement. The 5th factors are the average of place elevation, well number, propotion of agriculteral land area, household densty, and population density. Based on that findings in order to develope of coastal rural settlement especially in karst region, besides the development of tourism objects, the five factors should be taken in consideration.